KAJIAN KOMPARATIF PELAYANAN ANGKUTAN UMUM ANTARA KOTA SEMARANG DAN KOTA SURAKARTA - Setiarini, Ani; Riyanto, Bambang; Ismiyati, Ismiyati (Department of Civil Engineering, 2006)
ABSTRACT Semarang and Surakarta have different characteristic on structure and urban growth. This difference affects on urban public transport service in those cities. Aim of this research is to know the difference characteristic of urban public transport service between Semarang and Surakarta. The analysis method is comparing urban public transport service generally with transportation service and especially with public transport service, those are effectiveness and efficiency. Result of this research can be used for local government as one of the review on making of urban public transport system insight. The result of this research shows that the difference on urban structure of Semarang and Surakarta affect on urban public transport service. The urban structure of Semarang with concentric design and add with its ring radial road network cause almost all of public transport track through the down town area as the centre of all activities, mean while the urban structure of Surakarta with its grid road network tendency to spread the movement into all over the town that cause people activity spread relatively. These circumstances cause urban public transport track also spread all over the town following road network up to its hinterland. Some proposed to ascend urban public transport system service in Semarang needs an evaluation of urban public transport service more efficient with reduce or change public transport moda with that whose have bigger capacity so that can reduce traffic problem in down town area, mean while Surakarta needs to cooperate with its hinterland because almost all of urban public transport that are operating in Surakarta having the beginning and ending terminals outside of its jurisdiction. Keywords : Urban structure and public transport service